ANALYSIS OF THE DETERMINATION OF GUARDIANSHIP OF MAFQUD INHERITANCE ON THE URGENCY OF NATIONAL DAM LAND ACQUISITION IN THE RELIGIOUS COURT OF SUWAWA NORTH SULAWESI (CASE STUDY NUMBER: 355/PDT.P/2022/PA.SWW) - Choirullah, Ahmad Farhan; Suryana, Muhammad Indra (Hukum Islam, 2024)
Inheritance problems occupy the second highest level after divorce which is full of complexity, especially internally for the heirs. In the case in this study, the heir owned a plot of land that was left to heirs consisting of mother and child. However, as time goes by, the land which is the inheritance right of both of them is planned to be included in the category of national strategic project in the form of building a dam for the public interest. On the one hand, the heir is still a minor so he is not yet competent to take legal action if the land is sold, and on the other hand, the child's mother has disappeared (mafqud) and her whereabouts are unclear to this day. However, from the father's line there are still grandparents, both of whom submitted a request to the Religious Court to become guardians for the child so that they can look after, care for, look after and carry out buying and selling transactions of inherited land. The study in this study aims to explain the analysis of the determination of guardianship of mafqud heirs on the urgency of land acquisition for the national dam at the Suwawa Religious Court, North Sulawesi (Case Study Number: 355/Pdt.P/2022/PA.SWW. Meanwhile, the topic of study in this study is the determination of guardianship for heirs of minors, management of their inheritance and the inheritance of their parents who have mafqud status. In this study, the author uses a qualitative method with a descriptive approach to explain the legal arguments and facts. The results found in this study are that the Suwawa Religious Court granted and determined the petition of the applicants as guardians of Amelia Iskandar who is the heir of the minor and Indriyani Kosa, the heir who has mafqud status in order to be able to manage the inheritance left by the testator. Legal protection for mafqud heirs if in the future the person is found alive, then the applicants are obliged to provide the inheritance that is their share.